(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2016)
The present day and age is characterized by an abundance of economic and social problems of various kinds. An increase in materialism has inflicted serious harm on the physical and psychological health of people. Lifestyles are becoming increasingly fast paced and stressful. This constant stress has a very damaging effect on the body’s immune system leading to an increase in all kinds of diseases and illnesses.